Dorland's illustrated medical dictionary. - 4 0 16; (William Alexander Newman), 1864-1956. Dorland, W. A. Newman; 5 (Philadelphia : W.B. Saunders Co., 1994)
Provides definitions and explanations of 115,000 medical terms, arranged alphabetically, with illustrations, and related reference materials.
Adult;Adult
Keywords: 2 -- 0; 6; Medicine;Medicine -- Dictionaries.;Dictionaries.; 20; 2